2014
DOI: 10.1261/rna.047803.114
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting noncoding and pathogen RNA–protein interactomes

Abstract: RNA-protein interactions are central to biological regulation. Cross-linking immunoprecipitation (CLIP)-seq is a powerful tool for genome-wide interrogation of RNA-protein interactomes, but current CLIP methods are limited by challenging biochemical steps and fail to detect many classes of noncoding and nonhuman RNAs. Here we present FAST-iCLIP, an integrated pipeline with improved CLIP biochemistry and an automated informatic pipeline for comprehensive analysis across protein coding, noncoding, repetitive, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 43 publications
2
94
0
Order By: Relevance
“…CLIP-seq or HITS-CLIP, which stands for high-throughput sequencing of RNA that is isolated after ultraviolet (UV) irradiation-induced crosslinking and immunoprecipitation (Chi et al 2009;Moore et al 2014), and related methods, such as individual-nucleotide resolution iCLIP (Konig et al 2010), photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) (Hafner et al 2010), and FAST-iCLIP (Flynn et al 2015), are powerful techniques used to identify in vivo targets of RNA binding proteins (RBPs) that bind directly to RNAs or via an RNA guide, as is typically the case for Argonaute family proteins comprised of Ago and Piwi subclades (Liu et al 2008;Kim et al 2009). Agos are ubiquitously expressed and bind microRNAs or small interfering RNAs (siRNAs) to form RNA-induced silencing complexes (RISC)/miRNA Ribonucleoproteins (miRNPs) (Hammond et al 2001;Mourelatos et al 2002;Sontheimer 2005;Paroo et al 2007) and use the bound miRNA or siRNA as a guide to identify and silence target RNAs (Lee et al 1993;Elbashir et al 2001;Hammond et al 2001;Lewis et al 2003;Kiriakidou et al 2004;Rajewsky and Socci 2004).…”
Section: Introductionmentioning
confidence: 99%
“…CLIP-seq or HITS-CLIP, which stands for high-throughput sequencing of RNA that is isolated after ultraviolet (UV) irradiation-induced crosslinking and immunoprecipitation (Chi et al 2009;Moore et al 2014), and related methods, such as individual-nucleotide resolution iCLIP (Konig et al 2010), photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) (Hafner et al 2010), and FAST-iCLIP (Flynn et al 2015), are powerful techniques used to identify in vivo targets of RNA binding proteins (RBPs) that bind directly to RNAs or via an RNA guide, as is typically the case for Argonaute family proteins comprised of Ago and Piwi subclades (Liu et al 2008;Kim et al 2009). Agos are ubiquitously expressed and bind microRNAs or small interfering RNAs (siRNAs) to form RNA-induced silencing complexes (RISC)/miRNA Ribonucleoproteins (miRNPs) (Hammond et al 2001;Mourelatos et al 2002;Sontheimer 2005;Paroo et al 2007) and use the bound miRNA or siRNA as a guide to identify and silence target RNAs (Lee et al 1993;Elbashir et al 2001;Hammond et al 2001;Lewis et al 2003;Kiriakidou et al 2004;Rajewsky and Socci 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Third, with notable exceptions (e.g., iCLIP), the sequence resolution of these techniques typically precludes nucleotide-level resolution of binding motifs. Finally, differences in cross-linking efficiency and transcript abundance, both of which can vary over many orders of magnitude, are significant sources of bias in transcriptome-wide approaches (17)(18)(19).We overcame these biases with an approach that, for rare and abundant substrates alike, combines the genome-wide scale of Significance High-throughput sequencing has transformed modern biology, but its repertoire is currently confined to reading DNA molecules. Here, we report hardware and software adaptations that allow the very methods that enabled the genomic sequencing revolution to be applied to fluorescence-based biochemical assays, on a massive scale.…”
mentioning
confidence: 99%
“…Third, with notable exceptions (e.g., iCLIP), the sequence resolution of these techniques typically precludes nucleotide-level resolution of binding motifs. Finally, differences in cross-linking efficiency and transcript abundance, both of which can vary over many orders of magnitude, are significant sources of bias in transcriptome-wide approaches (17)(18)(19).…”
mentioning
confidence: 99%
“…Studies of posttranscriptional controls in this and other models have relied heavily upon a variety of in vitro experimental platforms to define mechanisms and biochemical pathways. While highly informative, such studies do not address the in vivo relevance and nonredundant functions of RNA-binding proteins in physiologically intact environments.The PCBPs (also known as ␣CPs and heterogeneous ribonucleoprotein [hnRNP] E proteins) are a widely expressed and multifunctional family of RNA-binding proteins (15-19) that bind numerous erythroid and nonerythroid mRNAs (20,21). Studies focused on globin gene expression have revealed that the PCBPs can integrate nuclear controls over splicing and 3= processing with cytoplasmic controls over mRNA stabilization via direct interactions of the PCBPs with cytosine-rich motifs in target .…”
mentioning
confidence: 99%
“…The PCBPs (also known as ␣CPs and heterogeneous ribonucleoprotein [hnRNP] E proteins) are a widely expressed and multifunctional family of RNA-binding proteins (15)(16)(17)(18)(19) that bind numerous erythroid and nonerythroid mRNAs (20,21). Studies focused on globin gene expression have revealed that the PCBPs can integrate nuclear controls over splicing and 3= processing with cytoplasmic controls over mRNA stabilization via direct interactions of the PCBPs with cytosine-rich motifs in target RNAs (22)(23)(24)(25).…”
mentioning
confidence: 99%